Cluster life cycles: dimensions and rationales of cluster development - Max-Peter Menzel; Dirk Fornahl (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
We present a model that explains how a cluster moves through a life cycle and why this movement differs from the industry life cycle. The model is based on three key processes: the changing heterogeneity in the cluster describes the movement of the cluster through the life cycle; the geographical absorptive capacity enables clustered companies to take advantage of a larger diversity of knowledge and the stronger convergence of clustered companies compared to non-clustered companies results in a reduction of heterogeneity. We apply these processes to four stages of the cluster life cycle: emergence, growth, sustainment and decline.
Keywords: R11; O30; L25; 330; cluster evolution; life cycle; heterogeneity; Regionale Konzentration; Lebenszyklus; Industrieökonomik; Theorie